2016
DOI: 10.1007/s00246-016-1451-2
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Speckle Tracking Echocardiography for Early Detection of Myocardial Dysfunction in Patients with Duchenne Muscular Dystrophy

Abstract: Cardiac complications are the leading cause of death in patients with Duchenne muscular dystrophy (DMD). Two-dimensional echocardiography is the current standard for monitoring of LV systolic function in these patients, but it might not detect early systolic dysfunction. The current study examined the use of speckle tracking echocardiography (STE) to detect early signs of cardiac dysfunction in DMD patients. A retrospective review of charts and offline strain analysis of transthoracic echocardiographic studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Other studies have demonstrated similar results, showing that echocardiographic myocardial strain can be used to detect early LVSD. 9,[24][25][26] The group with early LVSD was older and had a longer duration of disease and a higher frequency of gait loss, which correlates with findings by Spurney and colleagues, who showed that the development of cardiomyopathy in DMD patients was associated with the patient's age and the clinical stage of the disease. 23 Interestingly, a higher frequency of corticosteroid use was correlated with early LVSD.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Other studies have demonstrated similar results, showing that echocardiographic myocardial strain can be used to detect early LVSD. 9,[24][25][26] The group with early LVSD was older and had a longer duration of disease and a higher frequency of gait loss, which correlates with findings by Spurney and colleagues, who showed that the development of cardiomyopathy in DMD patients was associated with the patient's age and the clinical stage of the disease. 23 Interestingly, a higher frequency of corticosteroid use was correlated with early LVSD.…”
Section: Discussionsupporting
confidence: 84%
“…Our data show that echocardiographic myocardial strain analysis can detect LVSD before the reduction of the LVEF in a large number of DMD patients. Other studies have demonstrated similar results, showing that echocardiographic myocardial strain can be used to detect early LVSD …”
Section: Discussionsupporting
confidence: 59%
“…Significant decreases in longitudinal peak systolic strain/strain rate and early diastolic myocardial velocities previously were found in the LV inferolateral and anterolateral walls in patients with DMD [75] (Supplemental Figure 4). More recently, it was shown that GLS is lower in DMD patients than controls [76], and bull's-eye maps clearly show the particular involvement of the inferolateral wall in these patients (Table 3; Supplemental Figure 4).…”
Section: Systemic Diseases and Neuromuscular Disordersmentioning
confidence: 92%
“…For segmental longitudinal strain, Mertens et al study revealed that anterolateral segmental longitudinal strain is more severely impaired [ 31 ]. Taqatqa et al showed that apical segmental longitudinal strain is more pronounced [ 15 ]. Furthermore, Cho et al found that basal segmental longitudinal strain is serious [ 16 ].…”
Section: Discussionmentioning
confidence: 99%